CRIMINAL LAW POLICY IN THE SETTLEMENT OF TRAFFIC ACCIDENTS OF DEATH VICTIMS IN MUARO JAMBI REGENCY - Zulkarnain,; Rahman,; Muhammad Ikhlas, (International Journal of Social Science, 2022)
Traffic accidents often cause motorists and road users to suffer minor injuries or death. Based on the law, traffic violation cases should be resolved through legal channels. In reality, there is peace against traffic violations at the police level. This study is intended to determine the cause of the police allowing the peace of highway traffic crimes, to find out the peace made by the perpetrators of accidents related to victims of road traffic crimes. The research method used is normative research methods and empirical research methods. The data used are secondary data including primary legal materials, secondary legal materials, and tertiary legal materials, which were obtained through field research. To complete the data, it is used. field research by interviewing respondents and informants. The data that has been collected, analyzed and processed using a qualitative approach. There have been several cases of violations, including 6192 cases of motorcycles, 1532 cases of trucks, and St. Wagon 882 cases, pick up 393 cases, bus 350 cases and sedan 55 cases. The increase in the number of accidents was also followed by an increase in the percentage of victims who died due to traffic accidents. In handling it, there are obstacles, both internal and external.